The Conjugation of Pashto Compound Verbs - Zia Ul Islam Shirani; Lalkhan Minapal; Shafiqullah Amirzay (Randwick International of Education and Linguistics Science Journal, 2023)
Verb is a word which shows action happening time, generally has subject and time is known in verbs in fact this quality makes deference between verb and gerund. According to syntax, we have three types of verbs – Transitive verb, intransitive verb and Hukmi Motadi (Hukmi Transitive) verb. Most of the verbs has two roots (present and Past). According to structure, we have three types of verbs: simple verbs (as, root+suffix: ʣ+əm à ʣəm, χwr+əm à χwrəm à zə ɖoɖə́i χwrəm.) derivative verbs (as, article+root+suffix: rɑ+ʁ+əià rɑ́ʁəi à ahmád rɑ́ʁəi), and compound verbs (as, root+root+suffix: χpor + kedə́là [after changes of conjugation] χpəredə́l à wraʣpə́ɳa χpará ʃwa.). As well as, there are four categories of auxiliary verbs, as follow: “کېدل/kedə́l/”, “شول/ʃwəl/”, “ول/wəl/, کول/kawə́l/” and “کړل/kɽəl/”. Hereby, conjugation of verb in Pashto varies according to Number, Gender and Person. Meanwhile, both parts of compound verbs conjugate in which only one-part conjugates. Generally, the end of compound verbs is conjugated by the suffix according to the mentioned categories.